1999
DOI: 10.1046/j.1365-2796.1999.00543.x
|View full text |Cite
|
Sign up to set email alerts
|

Insulin sensitivity and haemostatic factors in men at high and low cardiovascular risk

Abstract: Abstract. Agewall S (Sahlgrenska University Hospital, Go Èteborg University, Sweden). Insulin sensitivity and haemostatic factors in men at high and low cardiovascular risk. J Intern Med 1999; 246: 489± 495.Objective. To investigate the relationship between variables of the coagulation and fibrinolysis system and insulin sensitivity in non-diabetic men at high and low risk of cardiovascular disease. Design. Cross-sectional study. Setting. Outpatient clinic in city hospital. Patients. Thirty-five men at high ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
2

Year Published

2000
2000
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 41 publications
2
9
0
2
Order By: Relevance
“…There is, however, also evidence indicating correlations with vWF ag and several components of the metabolic syndrome, such as insulin concentration, glucose disposal, fasting glucose concentration and urine albumin excretion [33][34][35]. These results further contribute to the uncertainty of whether vWF ag should be considered a true component of the metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…There is, however, also evidence indicating correlations with vWF ag and several components of the metabolic syndrome, such as insulin concentration, glucose disposal, fasting glucose concentration and urine albumin excretion [33][34][35]. These results further contribute to the uncertainty of whether vWF ag should be considered a true component of the metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…The primary physiologic function of PAI-1 and vWF is to maintain hemostatic balance in the vasculature (32,33), but because the endothelium is a primary source of PAI-1 and vWF, elevated levels also reflect stimulation or injury of endothelial cells (32,34). Elevated plasma levels of biomarkers of endothelial dysfunction are modestly correlated with impaired endothelium-dependent vasodilatation in forearm skin or the brachial artery (11,29) and are highly correlated with insulin resistance (12,35,36), providing one mechanism by which endothelial dysfunction might confer risk for type 2 diabetes. In the arteriolar microcirculation, impaired endothelium-dependent vasomotion may limit insulin-mediated capillary recruitment and redistribution of skeletal muscle blood flow from nonnutritive to nutritive flow routes, diminishing insulin delivery to insulin-sensitive muscle tissue (6,(37)(38)(39).…”
Section: Diabetes Vol 55 February 2006mentioning
confidence: 99%
“…In the literature, the association between anticoagulant proteins and insulin resistance and metabolic syndrome has been examined in only a small number of studies [44,45,46]. Interestingly, it has been shown that insulin resistance is accompanied by increased plasma concentrations of PC and PS [44], which may represent a protective response partly counteracting the increase in prothrombotic factors such as vWF [47], fibrinogen, coagulation factors VIII, XII and the B subunit of XIII [48]. In our study, vWF had a positive correlation with HOMA values.…”
Section: Discussionmentioning
confidence: 99%